Factors related to teamwork performance and stress of operating room nurses - Sonoda, Yukio; Onozuka, Daisuke; Hagihara, Akihito (Journal of Nursing Management, 2018)
Aim To evaluate operating room nurses' perception of teamwork performance and their level of mental stress and to identify related factors. Background Little is known about the factors affecting teamwork and the mental stress of surgical nurses, although the performance of the surgical team is essential for patient safety. Methods The questionnaire survey for operation room nurses consisted of simple questions about teamwork performance and mental stress. Multivariate analyses were used to identify factors causing a sense of teamwork performance or mental stress. Results A large number of surgical nurses had a sense of teamwork performance, but 30–40% of operation room nurses were mentally stressed during surgery. Neither the patient nor the operation factors were related to the sense of teamwork performance in both types of nurses. Among scrub nurses, endoscopic and abdominal surgery, body mass index, blood loss and the American Society of Anesthesiologists physical status class were related to their mental stress. Conversely, circulating nurses were stressed about teamwork performance. Conclusions The factors related to teamwork performance and mental stress during surgery differed between scrub and circulating nurses. Implications for nursing management Increased support for operation room nurses is necessary. The increased support leads to safer surgical procedures and better patient outcomes.